Case Report SUCCESSFUL MANAGEMENT OF EALES DISEASE WITH TUBERCULAR ETIOLOGY - Kusumajati, Anindya Putri; Metita, Mirza (International Journal of Retina, 2024)
Introduction: Recurrent vitreous hemorrhage is a defining indication of Eales disease, an idiopathic occlusive vasculitis of the peripheral retinal veins that primarily affects young males, and 38.7% of patients had a history of tuberculosis. This case study aims to illustrate the effective treatment of Eales disease, which includes vitreous hemorrhage and associated tuberculosis. Case report: A 23-year-old male presented with the primary complaint of impaired vision in his left eye since two weeks ago. Visual acuity was 1/60, and ultrasonography revealed vitreous hemorrhage. The right eye also has a history of vitrectomy and silicon oil from a vitreous hemorrhage two months prior. A full work-up was completed, with positive interferon-gamma release assay (IGRA) results. The patient received a 6-month course of antituberculous medication and an oral steroid on a tapering dose. The vitrectomy procedure was conducted on the left eye, but vitreous hemorrhage persisted even after the surgery. Three months following surgery, the vitreous hemorrhage cleared, and the visual acuity improved to 6/6 with a negative IGRA result. Discussion:Eales disease is identified in the condition of occlusive periphlebitis and retinal neovascularization, especially in the peripheral retina, in one or both eyes, after excluding other causes. Some patients may experience floaters, impaired vision, or even decreased visual acuity due to massive vitreous hemorrhage. In the earliest days of retinal perivasculitis, most patients are asymptomatic. Anti-tuberculosis treatment is considered for Eales disease with acute retinal periphlebitis with extensive infiltration, nodule development, and venous segment disappearance. In cases with persistent vitreous hemorrhage with decreased central vision for 3 months, vitrectomy is an option. Conclusion: One of the features of Eales disease is a young adult with recurrent vitreous hemorrhage that is tuberculous in nature. Early identification and a thorough eye examination, including USG and IGRA testing, as well as appropriate medicinal and surgical care, will result in a positive outcome.